2000
DOI: 10.1054/homp.1999.0365
|View full text |Cite
|
Sign up to set email alerts
|

Altered solution structure of alcoholic medium of potentized Nux vomica underlies its antialcoholic effect

Abstract: Nux vomica 30c, 200c and 1000c were administered orally to three batches of albino mice for three days. Six hours after the last dose on the third day the mice were injected i.p. with ethanol 4g/kg body wt. They lost their righting reflex and lay motionless apparently sleeping due to alcohol. Mice treated with three potencies of Nux vomica regained their righting reflex more quickly than the corresponding untreated controls. Each of the three batches of mice was tested twice for ethanol sedation, once with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…Nux vomica 30c and Nux vomica MT were able to reduce alcohol effects and voluntary ethanol intake in predisposed (susceptible) rats selected by the classical method described by Porsolt, in the decade of 60. 7,63 This data confirm the pilot results obtained by the same group. 64 The selection of sensitive rats as part of experimental design for studying high dilutions was first described by Cristea.…”
Section: Conceptual Aspectssupporting
confidence: 87%
“…Nux vomica 30c and Nux vomica MT were able to reduce alcohol effects and voluntary ethanol intake in predisposed (susceptible) rats selected by the classical method described by Porsolt, in the decade of 60. 7,63 This data confirm the pilot results obtained by the same group. 64 The selection of sensitive rats as part of experimental design for studying high dilutions was first described by Cristea.…”
Section: Conceptual Aspectssupporting
confidence: 87%
“…Other authors have observed differences between potentised and unpotentised solutions using NMR spectroscopy 5 ± 13 and T1 relaxation times. 14 In particular, as mentioned earlier, Sukul et al 14 noted differences in the T1 relaxation times of deuterium (among all hydrogen-containing molecules, a small proportion will contain this naturallyoccurring hydrogen isotope in place of hydrogen) in potentised and unpotentised ethanol solutions with and without nux-vom. It should be pointed out that these authors used high-resolution NMR instruments which are far more sensitive to the subtle molecular changes in solution that might be brought about by potentisation.…”
Section: Discussionmentioning
confidence: 84%
“…More recently still, T1 values of deuterium (an isotope of hydrogen) in ethanol with and without Nux vomica in homeopathic potency have been used as a measurable physical basis of the effective of high potencies. 14 Thus, NMR should be a useful tool for the investigation of homeopathic dilutions. However, it is not known whether these workers used soda-glass or boro-silicate NMR tubes in their experiments.…”
Section: Nmr and Homeopathymentioning
confidence: 99%
“…Unfortunately, to the knowledge of the author, no comparable independent repeat measurements were reported in either cases. More recent NMR measurements involving potentizations of Nux vomica in ethanole were reported by Sukul et al 18 Mice treated with Nux vomica dilutions appeared to show a sig-ni®cant reaction compared to a control group. A correlation with the T 1 relaxation of deuterium in the dilutions was reported.…”
Section: Fundamental Experimental Workmentioning
confidence: 82%